SUPERVISI GURU DALAM PENGEMBANGAN MUTU PENDIDIKAN - Nida Nadiya; Suklani Suklani (CV. ADIBA AISHA AMIRA, 2023)
Academic supervision needs to be carried out to provide technical assistance to teachers and other employees in carrying out the learning process, or to support the learning process which aims to improve the professional abilities of teachers and improve the quality of learning effectively. the purpose of this research is to find out 1). Definition, goals, objectives and principles of educational supervision, 2). Teacher supervision that can be done to improve the quality of education. Teacher performance is related to the quality, quantity of output, and reliability that the teacher has in carrying out his duties. Teachers who do not have high performance can reduce the quality of education, so supervision is needed to overcome this. This study used qualitative research methods. Data obtained based on literature study. The essence of the dimension of academic supervision is in the context of fostering teachers to improve the quality of the learning process. The target of academic supervision of the implementation of the learning process, which consists of the subject matter in the learning process, preparation of syllabus and lesson plans, selection of learning strategies/methods/techniques, use of media and information technology in learning, assessing learning processes and outcomes as well as classroom action research. Therefore, the teacher has an extraordinary role in the world of education. The low quality of education in a country is determined by the performance of teachers. Teachers who have high performance will produce high quality graduates.